Cerebrospinal fluid level of proNGF as potential diagnostic biomarker in patients with frontotemporal dementia - Malerba, Francesca; Florio, Rita; Arisi, Ivan; Zecca, Chiara; Dell’Abate, Maria Teresa; Logroscino, Giancarlo; Cattaneo, Antonino (Frontiers in Aging Neuroscience, 2024)
Frontotemporal dementia (FTD) is an extremely heterogeneous and complex neurodegenerative disease, exhibiting different phenotypes, genetic backgrounds, and pathological states. Due to these characteristics, and to the fact that clinical symptoms overlap with those of other neurodegenerative diseases or psychiatric disorders, the diagnosis based only on the clinical evaluation is very difficult. The currently used biomarkers help in the clinical diagnosis, but are insufficient and do not cover all the clinical needs.By the means of a new immunoassay, we have measured and analyzed the proNGF levels in 43 cerebrospinal fluids (CSF) from FTD patients, and compared the results to those obtained in CSF from 84 Alzheimer's Disease (AD), 15 Subjective Memory Complaints (SMC) and 13 control subjects.A statistically significant difference between proNGF levels in FTD compared to AD, SMC and controls subjects was found. The statistical models reveal that proNGF determination increases the